PROSTATE CANCER AND HIS INFLUENCE ON REPRODUCTIVE HEALTH - Nataliya Medvedovska; Volodymyr Podolskyi; Mykola Kvach; Iryna Stovban (Acta Medica Leopoliensia)
The aim of the study. Based on the data of the National Cancer Registry the research aims at conducting an analysis of morbidity and mortality of the male population of Ukraine for prostate cancer from 2014 to 2019.